PENGARUH FASILITAS KERJA, STRES KERJA DAN WORK LIFE BALANCE TERHADAP KINERJA KARYAWAN PT. BANK PEMBANGUNAN DAERAH SULAWESI TENGGARA CABANG BAUBAU - Rizki, Selvi Dilyanti; Makmur, Muhammad Rizaldi; Patulak, Lucia Evianti (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to analyse the effect of Work Facilities, Job Stress and Work Life Balance on Performance Employee of PT. Bank Pembangunan Daerah Sulawesi Tenggara (PT. BPD Sultra), Baubau Branch. The population in this were all employees of PT. BPD Sultra, Baubau Branch by using saturated sampling (census) where total respondents is used as a research sample in this case employees of PT. BPD Sultra, Baubau Branch as many as 30 employees. Data collection method by distributing questionnaires to respondents. The data analysis technique in this study used multiple linear regression analysis using the SPSS Version 26 program. The results of this study indicate that work facilities, work stress and work life balance simultaneously have a positive and significant effect on employee performance, work facilities have a positive and significant effect on employee performance, work stress has a negative but not significant effect on employee performance and work life balance has a positive effect and significant to employee performance.